Authority of The General Court in Detention of The Ship Juridical Analysis of Surabaya District Court Decision No.140 K/Pid.Sus/2012 - Kania Ankaa Prasetya; Aidul Fitriciada Azhari; Anugrah Nur Prasetyo (Proceeding International Conference Restructuring and Transforming Law, 2023)
Indonesian courts play an important role in determining the legality of detaining vessels as evidence and ensuring the rights of the parties are protected. The court has the authority to determine the legality of the detention and release the ship if there is insufficient evidence to prosecute or if it turns out that the detention is illegal. This research uses descriptive analytical research methods and a normative legal approach. This research uses the 1982 UNLCOS theory and expert opinions from Cornelis von Bynkershoek, Galliani and Azumi. This research focuses more on discussing ship detention procedures in general justice and ship detention as a form of collateral confiscation. Meanwhile, previous studies focused more on implementing regulations, conformity with civil regulations, the readiness of the courts to implement them, the benefits of implementing P and I in transportation contracts in Indonesian maritime areas and what forms of responsibility apply to carriers in Indonesian Sea Transportation. This research found that every ship will be detained if it does not have a Fishing Permit (SIPI) as intended in Article 27 paragraph (1) to catch fish in Indonesia. Ships that do not have SIPI will be subject to Articles of Law no. 31 of 2004 and Law no. 45 of 2009 so that the ship will be detained by the authorities. The anchoring of the ship is in accordance with Article 93 paragraph (3) of Law No. 45 of 2009 and has a legal basis in Article 1134 of the Civil Code, Article 1878 of the Civil Code, and Article 214 of the HIR/RBG. Based on these results, it can be explained that the process of detaining ships in Indonesia is handled through the courts, and the courts have the authority to issue orders for detaining ships in civil cases involving maritime lawsuits.